(untitled) (Modern education and development, 2024)
The article covers the etiological factors causing obesity, the pathogenetic mechanism of occurrence, determination of body mass index, determination of the degree of obesity and risk factors, as well as the obesity treatment program. In this condition, the factors causing obesity, the pathogenetic mechanism, the level of obesity, determination of body mass index, and the obesity treatment program are discussed.